Perspectives on Converting Keratin-Containing Wastes Into Biofertilizers for Sustainable Agriculture - Li, Qingxin (Frontiers in Microbiology, 2022)
Keratin-containing wastes can be pollutions to the environment if they are not treated properly. On the other hand, these wastes can be converted into value-added products applicable to many fields. Organic fertilizers and biofertilizers are important for sustainable agriculture by providing nutrients to increase the growth speed of the plant and increase the product production. Keratin-containing wastes therefore will be an important resource to produce organic fertilizers. Many microorganisms exhibit capabilities to degrade keratins making them attractive to convert keratin-containing wastes into products which can be applied to different fields. In this review, the progress in microbial degradation of keratins is summarized. In addition, perspectives in converting keratin into organic and biofertilizers for agriculture are described. With proper treatment, feathers which are keratin-containing wastes can be converted into high-value fertilizers to serve as nutrient for plant, reduce environment pressure and improve the quality of the soil for sustainable agriculture.